Acute toxicology testing - Gad, Shayne C., 1948- (Academic Press, 1998)
Acute toxicology testing provides the first line of defense against potentially dangerous chemicals. This book is a complete and practical guide to conducting and interpreting all regulatory required and commonly used acute toxicity tests. It presents detailed protocols for all of the common test designs and reviews their development and objectives. Acute Toxicology Testing, Second Edition will interest not only workers in the pharmaceutical industry, but also researchers and students in toxicology and public health. Key Features * Over 100 tables summarizing and interpreting results * Complete coverage of all major test designs and their limitations and advantages * Current status of alternative test designs and models.
Errata slip inserted.
Keywords: toxikologie; analytická toxikologie; toxické látky; toxicology; analytical toxicology; toxic substances; elektronické knihy; electronic books